Trends in serum creatinine testing in Oxfordshire, UK 1993-2013: A population based cohort study - Oke, J; Perera, R; McFadden, E; Stevens, R; Lasserson, D; Shine, B (BMJ Publishing Group, 2015)
Objectives: To determine how many kidney function tests are done, on whom, how frequently they are performed and how they have changed over time. Design: Retrospective study of all serum creatinine, urine albumin and urine creatinine tests Setting: Primary and secondary care in Oxfordshire from 1993 to 2013 Participants: Unselected population of 1,220,447 people Main outcome measures: The total number of creatinine and urinary protein tests ordered from primary and secondary care and the number of tests per year stratified by categories of estimated glomerular filtration rate (eGFR). The frequency of testing in patients having their kidney function monitored. Results:Creatinine requests from primary care increased steadily from 1997 and exceeded 220,000 requests in 2013. Tests corresponding to normal kidney function (eGFR > 60/mL/min/1.73m2) constituted 59% of all kidney function tests in 1993 and accounted for 83% of all tests in 2013. Test corresponding to CKD stages 3-5 declined after 2007. Reduced kidney function, albuminuria, male gender, diabetes and age were independently associated with more frequent monitoring. For a female patient between 61 and 80 years and with stage 3a CKD, the average number of serum creatinine tests (95% C.I) was 3.23 per year (3.19 to 3.26) and for a similar woman with diabetes, the average number of tests was 5.50 (5.44 to 5.56) tests per year. Conclusion: There has been a large increase in the number of kidney function tests over the last two decades. However, we found little evidence that this increase is detecting more CKD. Tests are becoming more frequent in people with and without evidence of renal impairment. Future work using a richer data source could help unravel the underlying reasons for the increased testing and determine how much is necessary and useful.